Continuous Spinal Anesthesia: A Comparative Study of Standard Microcatheter and Spinocath. Issue 2 (1st March 1999) - De Andrés, J.; Valía, J. C.; Olivares, A.; Bellver, J.
Abstract : Background and Objectives: This prospective, randomized study evaluated the advantages and disadvantages of a new subarachnoid catheter. Methods: Sixty ASA I-IV patients aged 40-70 years, scheduled for total knee arthroplasty, were randomly distributed into group 1 (Spinocath; Braun Melsungen, Germany) and group 2 (Intralong; Pajunk, Germany). The study tabulated details of subarachnoid catheter insertion, dural puncture, time to free cerebrospinal fluid (CSF) flow, anesthesia onset time, surgery anesthesia time, the upper level of sensory block reached, the anesthesiologist-evaluated degree of difficulty with the technique, and the quality of analgesia obtained and complications. At the end of surgery, all the catheters were removed, and their patency was checked. Results: Spinocath insertion required 6.3 ± 3.2 minutes in group 1 versus 3.9 ± 1.2 minutes in group 2 ( P < .01) with similar difficulties with catheter introduction. Perception of dural puncture was better in group 1 ( P < .05). There were significant intergroup differences in time to free flow of CSF through the catheter. In group 2, correct catheter positioning had to be confirmed by aspiration in 80% of cases ( P < .05). At the end of surgery, the catheters were removed, and there were no significant differences between groups. The anesthetic blocks were similar with both systems, Patient opinion of the technique did not differ between groups, and regression analysis did not show any differences between groups or correlation to any incident during performance of the technique. Globally, the anesthesiologists participating in the study considered both systems to be easy to use and adequate for continuous spinal anesthesia. With respect to the advantage afforded by a directional needle in orientating the catheter within the spinal canal, the Spinocath system—with a longer technique performance time than the standard approach—involves a success rate and incidence of technical problems similar to that of the conventional technique.